Single OnabotulinumtoxinA Session Add-On to Carbamazepine or Oxcarbazepine in Treatment-Refractory Trigeminal Neuralgia: A Case Series with 24-Week Follow Up - Georgia Xiromerisiou; Ioannis C. Lampropoulos; Emmanouil V. Dermitzakis; Michail Vikelis; Chrysoula Marogianni; Dimitrios Mysiris; Andreas A. Argyriou (Toxins, 2023)
We sought to assess the efficacy of combining onabotulinumtoxinA (BoNTA) as add-on therapy to carbamazepine or oxcarbazepine in treatment-refractory patients with trigeminal neuralgia (TGN) who failed to respond (less than 30% response rate) to adequate monotherapy. We conducted a retrospective study on 15 patients with a definite diagnosis of TGN, according to the established criteria, and underwent BoNTA as part of their treatment plan. A single BoNTA session was administered subcutaneously, according to patients’ perceived zone of pain, at different dosages ranging from 30 to 200 units (mean ± standard deviation: 87.3 ± 39.2). All patients (15/15; 100%) reported large reductions in the severity of their TGN-related neuropathic pain. The mean pain score on the VAS scale significantly decreased from 9.3 ± 1.1 to 3.7 ± 1.2 at 2 weeks after injecting BoNTA (p < 0.001) and remained stable at 4 and 24 weeks post-injection. Regarding the impact of BoNTA on patients’ health-related quality of life, there were significant improvements in both the physical and mental health domains (p < 0.05) of SF-36 tool. BoNTA may be a safe and effective treatment option for patients with refractory TGN when added on to carbamazepine or oxcarbazepine. The use of a single BoNTA session for TGN treatment may be an alternative to surgical interventions and as add-on treatment to oral medications, providing patients with a minimally invasive, effective, safe and well-tolerated option.